Adherence to guidelines in patients with chronic heart failure in primary health care - Maaike Giezeman; Mats Arne; Kersti Theander (Taylor & Francis Group, 2017)
Objective: To describe adherence to international guidelines for chronic heart failure (CHF) management concerning diagnostics, pharmacological treatment and self-care behaviour in primary health care. Design: A cross-sectional descriptive study of patients with CHF, using data obtained from medical records and a postal questionnaire. Setting: Three primary health care centres in Sweden. Subjects: Patients with a CHF diagnosis registered in their medical record. Main outcome measures: Adherence to recommended diagnostic tests and pharmacological treatment by the European Society of Cardiology guidelines and self-care behaviour, using the European Heart Failure Self-care Behaviour Scale (EHFScBS-9). Results. The 155 participating patients had a mean age of 79 (SD9) years and 89 (57%) were male. An ECG was performed in all participants, 135 (87%) had their NT-proBNP measured, and 127 (82%) had transthoracic echocardiography performed. An inhibitor of the renin angiotensin system (RAS) was prescribed in 120 (78%) patients, however only 45 (29%) in target dose. More men than women were prescribed RAS-inhibition. Beta blockers (BBs) were prescribed in 117 (76%) patients, with 28 (18%) at target dose. Mineralocorticoidreceptor antagonists were prescribed in 54 (35%) patients and daily diuretics in 96 (62%). The recommended combination of RAS-inhibitors and BBs was prescribed to 92 (59%), but only 14 (9%) at target dose. The mean score on the EHFScBS-9 was 29 (SD 6) with the lowest adherence to daily weighing and consulting behaviour. Conclusion: Adherence to guidelines has improved since prior studies but is still suboptimal particularly with regards to medication dosage. There is also room for improvement in patient education and self-care behaviour.